The Effect of Murabahah Financing on Return on Assets: Evidence from a Sharia Rural Bank in West Java, Indonesia (2017–2023) - Indah Tresna Ginarti; Endang Hendra; Dudi Sudirman (JOURNAL EKONOMI, KEUANGAN, PERBANKAN DAN AKUNTANSI SYARIAH, 2025)
Islamic rural banks (Bank Pembiayaan Rakyat Syariah, BPRS) play a critical role in channelling Sharia-compliant financing to micro and small enterprises in Indonesia, with murabahah (cost-plus-margin sale) constituting approximately 60% of total financing. Despite this dominance, empirical evidence on the effect of murabahah financing on profitability at the individual BPRS level remains limited, particularly for smaller rural banks outside major metropolitan areas. This study examines the effect of murabahah financing on Return on Assets (ROA) at BPRS Amanah Rabaniah, a Sharia rural bank in West Java, over the quarterly period Q1 2017–Q4 2023 (n = 28). A quantitative explanatory design was employed, using secondary data from published financial statements. Three analytical procedures were applied: classical assumption tests (normality, autocorrelation, heteroscedasticity), simple linear regression, and the t-test for coefficient significance. Results show a moderate positive correlation (R = 0.508) between murabahah financing and ROA, with the regression coefficient statistically significant (β = 4.121 × 10⁻⁵, t = 3.007 > t-table 1.701, p = 0.006). The coefficient of determination (R² = 0.258) indicates that 25.8% of ROA variation is explained by murabahah financing, with 74.2% attributable to other factors including musyarakah financing, operational efficiency, and non-performing financing ratios. The findings confirm that murabahah financing exerts a positive and significant effect on BPRS profitability but is not the sole determinant, highlighting the importance of portfolio diversification and cost management for sustainable financial performance